Safety Assessment of Carbonate Salts as Used in Cosmetics. (June 2022) - Johnson, Wilbur; Bergfeld, Wilma F.; Belsito, Donald V.; Hill, Ronald A.; Klaassen, Curtis D.; Liebler, Daniel C.; Marks, James G.; Shank, Ronald C.; Slaga, Thomas J.; Snyder, Paul W.; Gill, Lillian J.; Heldreth, Bart
The Expert Panel for Cosmetic Ingredient Safety (Panel) assessed the safety of 6 carbonate salts which function as absorbents, bulking agents, opacifying agents, pH adjusters, buffering agents, abrasives, and oral care agents in cosmetic products. The Panel reviewed relevant data relating to the safety of these ingredients, and concluded that these carbonate salts are safe in the present practices of use and concentration in cosmetics when formulated to be non-irritating.